Development of 5-FU Loaded poly lactic-co-glycolic acid Nanoparticles for Treatment of Lung Cancer - Bhattacharya, Sankha (Iraqi Journal of Pharmaceutical Sciences, 2022)
Non-Small Cell Lung Cancer (NSCLC) accounts for about 84% of all lung cancer types diagnosed so far. Every year, regardless of gender, the NSCLC targets many communities worldwide. 5-Fluorouracil (5-FU) is a uracil-analog anticancer compound. This drug tends to annihilate multiple tumour cells. But 5-FU's most significant obstacle is that it gets very easily metabolized in the blood, which eventually leads to lower anticancer activity. Therfore a perfect drug delivery system is needed to overcome all the associated challenges.In this experiment, an attempt was made to prepare 5-FU loaded poly lactic-co-glycolic acid  nanoparticles using solvent evaporation method and subsequently observed the effect of molecular weight of poly lactic-co-glycolic acid, loading of poly lactic-co-glycolic acid, sonication period on the cytotoxic effect of 10 % w/w 5-FU loaded PLGA nanoparticles against human A549 Isogenic cell line.In this experiment, two points are more evident: first, poly lactic-co-glycolic acid has a major impact on 5-FU release due to higher degradation and rate of diffusion in nanoparticle solution; and second, nanoparticles with a larger surface area and smaller particle size have a lower half-maximal inhibitory concentration (IC50) value. The IC50 of all nanoparticles was significantly higher (p=0.0145) than that of the free 5-FU controlled group (8.34Nm). The cytotoxicity would be greater if the IC50 value was lower. Nanoparticles with an 18-minute sonication time was found to  be more cytotoxic than those with PLGA nanoparticles containing 12% polyvinyl alcohol. In this experiment 10% w/w 5-FU loaded poly lactic-co-glycolic acid nanoparticles was prepared for laboratory research to translational research for the treatment of lung cancer.